Prevalence of Oral Trichomoniasis in Patients with Periodontitis and Gingivitis Using PCR and Direct Smear - A Athari; L Soghandi; A Haghighi; B Kazemi (Tehran University of Medical Sciences, 2007)
Background: Trichomonas tenax, a commensal flagellated protozoan, inhabits in human oral cavity. This parasite is cos-mopolitan and frequently found in patients with poor oral hygiene and advanced periodontal disease. There is only one published study that rebound the prevalence of this parasite in Iran. This PCR based study compared the prevalence of oral trichomoniasis in patients with oral diseases and a healthy control group.Methods: From May 2005 to April 2006, the subgingival dental plaques of 160 patients with gingivitis or periodontitis and 160 controls who attended to Dental School of Shaheed Beheshti Medical University, Iran were taken and examined by wet mount smear, and Giemsa staining. Likewise, a PCR protocol was developed for specific detection of T.tenax using a pair of primers designed for its 18S rRNA gene. Results: Thirty three (20.6%) of patients were PCR positive while 28 (15.5%) were diagnosed using wet preparation and Giemsa staining. In the other hand, 2 (1.9%) of control group were identified positive by PCR procedure.  The prevalence of oral trichomoniasis in our study (20.6%) was compatible with many other published reports which mostly has ranged from 12%-32%.  Conclusion: The study revealed dependence between the frequency of occurrence of T. tenax and the state of periodontitis. The present PCR procedure could provide a simple and rapid detection method of T. tenax in dental plague.